(untitled) (Research, Society and Development, 2021)
Dengue is an acute, systemic, unique and self-limited viral pathology in its classic form, transmitted by arthropods. However, the year 2020 was marked by the pandemic of the new Coronavirus (COVID-19) and, there was a decrease in the cases of notified diseases caused by arboviruses when contrasted with the same period in 2019. The present work aims to proposal to invite health professionals and the community in general to reflect on the importance of notification seeking and assisting dengue in the state of Sergipe amid the pandemic of the new coronavirus, in order to demonstrate the high levels of underreporting and absence of the demand for assistance that may impact the quality of life of the general population. This is a cross-sectional observational study, with a quantitative analytical approach, with data collected from 2019-2020 through the analysis of Epidemiological Bulletins and notifications from SINAN (System of Diseases and Notifications) and SIM (Mortality Information System). The data obtained showed that there was a reduction, comparing the years 2019-2020, from 5164 cases notified in 2019 to 959 cases (18.5% of the first) in 2020, in the notifications in the cases of Dengue in the period studied from epidemiological week 12-30. The aforementioned information showed that, probably, the efforts directed at containing the new emerging entity, COVID-19, hindered the notifications and the effective diagnoses of the aforementioned pathology.